Microplastics mixture exposure at environmentally relevant conditions induce oxidative stress and neurotoxicity in the wedge clam Donax trunculus. (November 2020) - Tlili, Sofiene; Jemai, Dorsaf; Brinis, Samar; Regaya, Imed
Abstract: Contamination by micro and nano plastics is actually considered as a global environmental preoccupation. The quantification of microplastics in natural habitats and the characterization of their potential effects in marine wild organisms is currently of high importance. The main objective of this work was to investigate the fate and the effects of a microplastic mixture (ratio of 1: polyethylene (PE), 1: polypropylene (PP)) in the wedge clam Donax trunculus . The assimilation kinetics of microplastics particles was assessed in different organs (gills, digestive gland and flesh) using three different protocols (direct observation, H2 O2, and HNO3 /HCl digestion) in order to compare method's efficacity. The main biological endpoints studied were Aceylcholinesterase (AChE) inhibition as a neurotoxicity biomarker, the Catalase (CAT) enzymatic activity and the Gluthation-S-Transfereases (GSTs) activities as oxidative stress and phase II detoxification phase markers, respectively. Results showed that the H2 O2 digestion method was more efficient to assess particles assimilation than the direct observation and acid digestion. In all cases no particles were detected in clam's flesh and gills were the first target organ for micro-plastics accumulation. The exposure of Donax truculus to PP/PE mixture (0.06 g/Kg of sand) induce a significant inhibition of AChE activity in both gills and digestive gland and oxidative stress in all organs studied. This study brings new results on the potential accumulation of PP and PE associated to neurotoxicity and oxidative stress of the wedge clam Donax trunculus . Highlights: The wedge clam Donax trunculus was exposed to a micro-plastics mixture in an environmental relevant conditions. The assimilation kinetics and the response of oxidative stress and neurotoxicity biomarkers were studied. The acid digestion method is more efficient to asses particles assimilation than direct observation. Micro plastics ingestion inhibit significantly Acetylcholinesterase activity in both gills and digestive gland. The exposure to micro plastics induce oxidative stress in the wedge clam.